Review of Australian seaweed aquaculture: Limitations and opportunities with a focus on two candidate species Asparagopsis taxiformis (Delile) Trevisan (1845) and Chaetomorpha linum (O.F. Müller) Kützing (1845) - Joel Wynhorst; Benjamin Camer-Pesci; Ravi Fotedar; Janet Howieson (Journal of Agriculture and Food Research)
Australia contributes approximately 0.01 % of annual biomass production in the global seaweed market despite its wide diversity of species and proximity to massive consumer markets in Asia. The Australian Government has outlined several strategies to rapidly increase domestic seaweed production, with a strong focus on Asparagopsis sp. due to its well documented capacity to reduce ruminant methane production. Industry development however is currently limited by major knowledge gaps regarding the unique environmental, social and regulatory conditions in Australia. Factors such as off-shore winds, low population density, strict legal regulations regarding marine conservation, and high initial investment costs may impact proposed large-scale ocean-based farms. This review therefore provides a detailed discussion on these limitations within the context of ocean-based seaweed farming. The candidacy of Asparagopsis taxiformis as a target species is discussed with reference to its complex life cycle and knowledge gaps pertaining to its practicality and safety as a livestock feed supplement. Chaetomorpha linum is discussed a less well documented candidate for mass commercial cultivation because of its known robust biochemical profile and potential applications in multitrophic aquaculture. The cultivation of C. linum in novel production systems, such as using inland saline water is also discussed. Several recommendations are made to aid in the development of the Australian seaweed industry, including a focus of research on easily replicable, low-cost, land-based culture systems and production of high value products with strong end-usage functionality. Further, the development of novel production systems, such as land-based inland saline water aquaculture, may provide a new path forward for the industry, though several major knowledge gaps, particularly regarding bioeconomic feasibility persist and must first be addressed.